2016
DOI: 10.1038/leu.2016.77
|View full text |Cite
|
Sign up to set email alerts
|

Opposite activation of the Hedgehog pathway in CD138+ plasma cells and CD138−CD19+ B cells identifies two subgroups of patients with multiple myeloma and different prognosis

Abstract: Hyperactivation of the Hedgehog (Hh) pathway, which controls refueling of multiple myeloma (MM) clones, might be critical to disease recurrence. Although several studies suggest the Hh pathway is activated in CD138- immature cells, differentiated CD138+ plasma cells might also be able to self-renew by producing themselves the Hh ligands. We studied the gene expression profiles of 126 newly diagnosed MM patients analyzed in both the CD138+ plasma cell fraction and CD138-CD19+ B-cell compartment. Results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Consistent with these results, we observed high expression of Hh proteins in PCs from all MM patients that harbor del(17p), but only part of PCs from other MM patients showed similar Hh expression. Moreover, our results also indicated that the expression levels of Smo and Gli1 protein varied significantly in primary CD138+ cells from bone marrow of different MM patient, consistent with the report by Martello et al . The difference reflects the heterogeneity of MM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with these results, we observed high expression of Hh proteins in PCs from all MM patients that harbor del(17p), but only part of PCs from other MM patients showed similar Hh expression. Moreover, our results also indicated that the expression levels of Smo and Gli1 protein varied significantly in primary CD138+ cells from bone marrow of different MM patient, consistent with the report by Martello et al . The difference reflects the heterogeneity of MM.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, miR‐324‐5p was lower in MM patients without del(17p) than normal PCs, indicating its expression was not only regulated by gene dosage. Martello et al . found that MM patients harboring del(17p) had a higher frequency in the group of Hh hyperactivation in plasma cells, which displayed an unfavorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the second approach, only MM-related files in the Human Genome U133 Plus 2.0 format were normalized to calculate the risk factor for short progression-free survival based on the average log 2 expression of 70 probesets (GEP70 signature), as described elsewhere [ 36 ]. Pearson correlation coefficients were calculated between the resulting score and the expression value of each PC signature gene using three independent datasets: E-GEOD-17306, E-MTAB-363, E-GEOD-68891 [ 34 , 37 , 38 ]. Genes associated with prognosis risk factor were those with correlation coefficients significantly different from zero in the three datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Martello M et al also proposed that controlling the Hh pathway in MM to prevent its overactivation might play a role in preventing MM recurrence. The researchers showed that patients could be divided into two groups according to the expression level of the Hh gene, among which patients with excessive activation of plasma cell Hh had poor prognosis and survival period, suggesting the promoting effect of Hh activation on MM recurrence [ 89 ]. Knocking down the GLI, signal transduction protein of hedgehog can cause the rate of SP cells to decrease [ 90 ].…”
Section: Active Signaling Pathways Related To Mmscs and Drugs Targeting Themmentioning
confidence: 99%